Efecto de la renta de los recursos naturales, el empoderamiento político femenino, la corrupción política, y el PIB sobre la desigualdad de ingresos durante 1990- 2022 en Ecuador: una aplicación de modelos de series de tiempo - Eras Guerrero, Christel Nicole (2024)
Income inequality in Ecuador has reached alarming levels, evidenced by a 47.72-fold gap between the richest 5% and the poorest 5% in the fourth quarter of 2022. This increase underscores the persistent concern about inequality and economic deterioration in the country. Thus, this research focuses on evaluating the effect of natural resource rent, female political empowerment, political corruption, and GDP on inequality during 1990-2022 in Ecuador, using statistical and econometric techniques, in order to propose structural policies aimed at mitigating inequality in the country. The data for this study comes from the World Income Inequality Database (WIID) to measure income inequality, V-Dem to measure variables such as the female political empowerment index and political corruption, and the World Bank for natural resource rents and GDP. In addition, statistical techniques and econometric models are employed in order to provide a robust analysis that allows the fulfillment of the research objective. The results found identified a moderately positive correlation between natural resource income and GDP with inequality, while female political empowerment and corruption reduction counteract it. Furthermore, a long-lasting connection was found between the variables in the long run, although no direct causal relationship was detected between natural resource income and inequality. Therefore, structural policies that promote economic diversification, reduce dependence on natural resources and strengthen female political empowerment, together with anti-corruption measures, are recommended. Prioritizing inclusive and sustainable economic growth focused on job-creating sectors is crucial. This combination of strategies will build a more equitable and resilient socioeconomic base, thus mitigating inequality.